1996
DOI: 10.1007/bf01736989
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular filtration rate in relation to extracellular fluid volume: Similarity between99mTc-DTPA and inulin

Abstract: The rate constant (alpha2) of the terminal exponential of the technetium-99m diethylene triamine penta-acetic acid (DTPA) plasma clearance curve is close to the ratio of glomerular filtration rate (GFR) to extracellular fluid volume (ECV) and is therefore a convenient, already normalised, measure of filtration function. Since alpha2 depends on the distribution volume of the tracer, our aim was to compare alpha2 from inulin and 99mTc-DTPA and also to compare the equilibration kinetics of the two filtration mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…It should be emphasized, however, that this does not invalidate the use of GFR/ECFV, as in this ratio P IOT falls out of the equation. For this reason, as also pointed out by others, assessment of GFR/ECFV is less sensitive to procedural errors than assessment of GFR alone (5,11). Third, this is a single-center study, investigating one tracer and one measurement protocol only.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It should be emphasized, however, that this does not invalidate the use of GFR/ECFV, as in this ratio P IOT falls out of the equation. For this reason, as also pointed out by others, assessment of GFR/ECFV is less sensitive to procedural errors than assessment of GFR alone (5,11). Third, this is a single-center study, investigating one tracer and one measurement protocol only.…”
Section: Discussionmentioning
confidence: 86%
“…Because the distribution volume (V d ) of these tracers for GFR ideally equal extracellular fluid volume (ECFV) (2)(3)(4)(5)(6)(7)(8)(9), measuring GFR with such tracers could potentially be used for simultaneous assessment of ECFV.…”
mentioning
confidence: 99%
“…The ECV, the actual fluid volume filtered by the kidney, should correlate Ž . with renal function Gunasekera et al, 1996 , andŽ . Pernia et al 1989 found this to be the case Ž 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Measured Tc-99m DTPA serum clearance by multipleplasma sample method (MPSM) is similar to inulin clearance; however, it is not practical to collect multiple plasma samples on a daily routine (14). To facilitate the procedure, Tc-99m DTPA clearance by the two-plasma sample (TPS) method was compared to MPSM and a significant correlation was reported (15).…”
Section: Introductionmentioning
confidence: 99%